Prevalence and predictors of overweight and obesity among school-aged children in urban Ghana - Aryeetey, R.; Lartey, A.; Marquis, G.S.; et al. (BMC Obesity, 2017)
Background: Childhood overnutrition is a serious public health problem, with consequences that extend into adulthood. This study aimed to determine the prevalence and determinants of overweight and obesity among school-age children in two urban settings in Ghana. Methods: This cross-sectional study involved 3089 children (9–15 years) recruited between December 2009 and February 2012 in Accra and Kumasi, Ghana. Socio-demographic, dietary, and physical activity data were collected using pretested questionnaires. BMI-for-age z-scores were used to categorize anthropometric data of the children as thin, normal, or overweight/obese. Determinants of overweight were examined using multiple logistic regressions. Results: Seventeen percent of children were overweight or obese. Children who reported lower participation (< 3 times/week) in sports activity were 44% more likely to be overweight or obese (AOR = 1.44; 95% CI: 1.07, 1.94). Maternal tertiary education (AOR = 1.91, 95% CI: 1.07, 3.42), higher household socioeconomic status (AOR = 1. 56, 95% CI: 1.18, 2.06), and attending private school (AOR = 1.74, 95% CI: 1.31, 2.32) were also associated with elevated risk of overweight and obesity. Conclusions: Physical inactivity is a modifiable independent determinant of overweight or obesity among Ghanaian school-aged children. Promoting and supporting a physically active lifestyle in this population is likely to reduce the risk of childhood overnutrition.
Research Article
Keywords: School-age children; Overweight; Obesity; Physical activity; Urban; Ghana